Risk factors for keratinocyte skin cancer in patients diagnosed with melanoma, a large retrospective study. (January 2016) - Espinosa, Pablo; Pfeiffer, Ruth M.; García-Casado, Zaida; Requena, Celia; Landi, Maria Teresa; Kumar, Rajiv; Nagore, Eduardo
Abstract: Background: Melanoma survivors are at an increased risk of developing other malignancies, including keratinocyte skin cancer (KSC). While it is known that many risk factors for melanoma also impact risk of KSC in the general population, no previous study has investigated risk factors for KSC development in melanoma patients. Objective: We assessed associations of personal and clinical characteristics, including skin phenotype and variations in the melanocortin 1 receptor ( MC1R ) gene, with KSC risk in melanoma patients. Patients and methods: We used prospective follow-up information on 1200 patients treated for melanoma at the Instituto Valenciano de Oncología, Spain, between 2000 and 2011. We computed hazard ratios and 95% confidence intervals (CIs) for the association of clinical, personal and genetic characteristics with risk of KSC, squamous cell carcinoma (SCC), or basal cell carcinoma (BCC) from Cox proportional hazard models. Five-year cumulative incidence based on competing risk models of SCC, BCC or KSC overall was computed using multivariate subdistribution hazard models. To assess predictive performance of the models, we computed areas under the receiver-operating characteristic curves (AUCs, discriminatory power) using cross-validation. Results: Median follow-up was 57.2 months; a KSC was detected in 163 patients (13.6%). In multivariable Cox models, age, sex, sunburns, chronic sun exposure, past personal history of non-melanoma skin cancer or other non-cutaneous neoplasia, and the MC1R variants p.D294H and p.R163Q were significantly associated with KSC risk. A cumulative incidence model including age, sex, personal history of KSC, and of other non-cutaneous neoplasia had an AUC of 0.76 (95% CI: 0.71–0.80). When p.D294H and p.R163Q variants were added to the model, the AUC increased to 0.81 (95% CI: 0.77–0.84) (p-value for difference <0.0001). Conclusions: In addition to age, sex, skin characteristics, and sun exposure, p.R163Q and p.D294H MC1R variants significantly increased KSC risk among melanoma patients. Our findings may help identify patients who could benefit most from preventive measures. Highlights: Melanoma survivors are at increased risk of developing keratinocyte skin cancer (KSC). The estimated cumulative incidence exceeds by far that of the general population. Some characteristics, including melanocortin 1 receptor variants, define melanoma patients at higher risk of developing KSC.